PENGEMBANGAN MEDIA PEMBELAJARAN POWERPOINT INTERAKTIF DALAM PEMBELAJARAN IPAS KELAS IV “PERUBAHAN WUJUD ZAT” DI SDN TAMBAKROMO 03 KABUPATEN PATI - Rachma Dinda Lestari; Choirul Huda; Riris Setyo Sundari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Elementary School Teacher Education Study Program, Faculty of Education, PGRI University Semarang. 2023. The background of making this thesis is due to a problem, namely the not yet developed technology-based learning media in the form of Interactive Powerpoint which is applied in learning. This is influenced by the lack of teachers utilizing technology that is already available in the Interactive Microsoft Office Powerpoint to be used as learning media. Teachers prefer to use the lecture method only and rarely use learning media. The researcher focused his research on one class IV science material, namely "Changes in the Form of Substances". This type of Research and Development (R&D) research is a development research used by researchers. The subjects were class IV teachers at SDN Tambakromo 03 and their students. Data collection techniques are by using direct observation, questionnaires, interviews and documentation. The results of data analysis using data presentation, data editing, and the last is looking for conclusions from the results of research that has been carried out by researchers. The results of the media and material validators in this learning media are derived from assessment instruments between two expert lecturers or material and media expert validators producing the same final data and stating " worth using without revision". The final data validation between media experts 1 and 2 produces an average percentage value of 93.901%. While the results of the final grades of material experts 1 and 2 produce an average percentage of 92.300%. After validation, the reliability value is sought to find out whether the data is reliable or not. The results of the final reliability score of media experts 1 and 2 are 99.9%. While the results of the final score of material experts 1 and 2 are 99.7%. The results of the trial explain that this interactive PowerPoint learning media is feasible to use.